La vulneración de los derechos humanos durante la pandemia y la cuarentena en Colombia (2021)
At the begining of 2020 and until the first of september, Colombia as the rest of the world has had to deal with many problems due to pandemic that surprised humanity originated in China. Colombia faced many problems of social and economic order, the authorities dictated regulations that forced the population to remain locked up in quarantine to avoid contagion. At that point, many fundamental human rights were violated by the autorities of some municipalities and departaments and by the population that did not accept or respect biosafety protocols. The authorities exceeded their power, there were abuses on both sides which generated more complicated problems related to security and coexistence between the state, the authorities and the population.